PENGUJIAN PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA DENGAN PROFITABILITAS SEBAGAI VARIABEL PEMODERASI - Stephanus Andi Adityaputra (Jurnal Akuntansi dan Pajak, 2023)
Profit becomes the target for earnings management. This happens because management has more information than shareholders. One of the earnings management cases in Indonesia occurred at PT Garuda Indonesia (Persero) Tbk in 2018. Therefore, a good corporate governance mechanism needs to be implemented to minimize earnings management. The purpose of this study is to examine and identify the effect of managerial ownership and institutional ownership on earnings management. The research sample was taken using a purposive sampling technique so that a total of 66 samples were obtained from infrastructure, utility and transportation sector companies listed on the Indonesia Stock Exchange during 2018 – 2021 after removing outlier data. Research data were analyzed using Moderated Regression Analysis (MRA) with IBM SPSS Statistics 25 software. The results of this study indicate that managerial ownership has a negative effect on earnings management, while institutional ownership has no effect on earnings management. In addition, profitability in this study was not able to moderate the effect of managerial ownership and institutional ownership on earnings management.